2017
DOI: 10.4244/eij-d-16-00299
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement with the Portico valve: one-year results of the early Canadian experience

Abstract: Transcatheter aortic valve replacement with the repositionable Portico valve provides satisfactory short- and medium-term haemodynamic and clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
4
7
1
3
Order By: Relevance
“…Sameer Hirji 1 , MD, MPH; Gregory Leya 2 , MD, MBA; Marc Pelletier 1 *, MD, MSc We found the recent study by Maisano et al very thought-provoking, given the focus on the commercial experience using the Portico™ bioprosthetic valve (Abbott, Santa Clara, CA, USA) in the multicentre PORTICO-1 study 1 . We applaud the authors for conducting this important study which further adds to a growing body of evidence demonstrating the overall safety (low mortality) and acceptable clinical and haemodynamic outcomes (low transvalvular gradients and low rate of moderate-high paravalvular leak) of the Portico valve [2][3][4] .…”
Section: Are We Compromising On Value Versus Performance: Time To Consider the Portico Valve As A Third Major Market Player?mentioning
confidence: 95%
See 1 more Smart Citation
“…Sameer Hirji 1 , MD, MPH; Gregory Leya 2 , MD, MBA; Marc Pelletier 1 *, MD, MSc We found the recent study by Maisano et al very thought-provoking, given the focus on the commercial experience using the Portico™ bioprosthetic valve (Abbott, Santa Clara, CA, USA) in the multicentre PORTICO-1 study 1 . We applaud the authors for conducting this important study which further adds to a growing body of evidence demonstrating the overall safety (low mortality) and acceptable clinical and haemodynamic outcomes (low transvalvular gradients and low rate of moderate-high paravalvular leak) of the Portico valve [2][3][4] .…”
Section: Are We Compromising On Value Versus Performance: Time To Consider the Portico Valve As A Third Major Market Player?mentioning
confidence: 95%
“…In particular, the Portico valve, an acceptable and viable option in many countries, is gaining appreciable interest and has shown comparable haemodynamic performance to the newer-generation valves [2][3][4] . Unfortunately, the lack of head-to-head comparison has hindered its growth due to concerns over safety and performance.…”
Section: Are We Compromising On Value Versus Performance: Time To Consider the Portico Valve As A Third Major Market Player?mentioning
confidence: 99%
“…The height of the valve is designed to result in minimal protrusion into the LVOT, reducing the incidence of post-procedural pacemaker implantation. Currently Portico bears a CE mark, available in Europe and is continuing its IDE trial in the United States [38].…”
Section: St Jude Medical Portico Valvementioning
confidence: 99%
“…In a large meta‐analysis including 12,926 patients treated with Edwards and Medtronic valves, the overall rate of more‐than‐mild AR was ~11% . Previous studies with the new self‐expandable Portico™ valve have shown rates of more‐than‐mild AR of 3.6%–10% …”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies with the new self-expandable Portico™ valve have shown rates of more-than-mild AR of 3.6%-10%. [2][3][4] More-than-mild AR after TAVR has been shown to increase both morbidity and mortality. 1 Thus, there is an urgent need to quantify AR after TAVR to identify patients with moderate-to-severe residual AR requiring a corrective measure, provided that, the implantation depth is acceptable.…”
Section: Introductionmentioning
confidence: 99%